Normalization of cerebral vasoreactivity using BOLD MRI after intravascular stenting - Attyé, Arnaud (Hum Brain Mapp, 2013)
Background and purpose: Intravascular angioplasty and stenting of intracranial arterial stenosis provided controversial results. Besides the expertise of the practitioners, the selection of the patients remains challenging. BOLD MRI of the cerebral vasoreactivity (BOLD MRI CVR) to hypercapnia provides reproducible maps of the entire brain of the vascular reserve, and could be helpful to assess the best therapeutic strategy. Case history: We report the case of a 63‐year‐old woman referred for a severe stenosis of the proximal portion of the left middle cerebral artery, revealed by a lenticulostriate and precentral infarction. Despite an aggressive medical treatment during 5 months, the occurrence of iterative transient ischemic attacks motivated intravascular stenting. Functional MRI of the vasoreactivity to hypercapnia using both Blood Oxygen Level Dependent (BOLD) and arterial spin labeling sequences showed normal basal perfusion and impaired vasoreactivity in the left middle cerebral artery territory. Three months after stenting, the BOLD MRI CVR showed vasoreactivity normalization. Since, the patient remains free of ischemic disorders one year after stenting. Conclusion: BOLD MRI of the CVR to hypercapnia may be helpful to optimize the treatment of patients with intracranial arterial stenosis, and could be performed in future therapeutic trials. Hum Brain Mapp 35:1320–1324, 2014. © 2013 Wiley Periodicals, Inc.